Integration of phospholipid-complex nanocarrier assembly with endogenous N-oleoylethanolamine for efficient stroke therapy - Xiangrui Yang; Lanxi Xu; Juan Zhou; Yunlong Ge; Shichao Wu; Junxiong Huang; Ying Li; Maoshu Zhu; Xin Jin; Lichao Yang (Journal of Nanobiotechnology, 2019)
Abstract Background Leading to more and more deaths and disabilities, stroke has become a serious threat to human health. What’s more, few effective drugs are available in clinic till now. Results In this research, we prepared a novel neuroprotective nanoformation (OEA–SPC NPs) via the combination of the nanoparticle drug delivery system with the endogenous N-oleoylethanolamine (OEA). By forming hydrogen bond between OEA and the carrier—soybean phosphatidylcholine (SPC), the form of OEA was turned into amorphus state when loading to the nanoparticles, which greatly improved its bioavailability. Then the following systematic experiments revealed the efficient neuroprotective effect of OEA–SPC NPs in vivo. Compared with the MCAO group, the cerebral infarct volume was reduced by 81.1%, and the edema degree by 78.4% via the oral administration of OEA–SPC NPs. And the neurological deficit scores illustrated that the MCAO rats treated with OEA–SPC NPs exhibited significantly less neurological dysfunction. The Morris water maze test indicated that the spatial learning and memory of cerebral ischemia model rats were almost recovered to the normal level. Besides, the OEA–SPC NPs could inhibit the inflammation of reperfusion to a very slight level. Conclusions These results suggest that the OEA–SPC NPs have a great chance to be a potential anti-stroke formation for clinic application and actually bring hope to thousands of stroke patients.